FORUM MŁODYCHTransthoracic lung ultrasound during postoperative intensive care in children with congenital heart disease - Paczkowski, Konrad; Czeczko, Katarzyna; Kosiak, Wojciech; Haponiuk, Ireneusz; Chojnicki, Maciej; Jaworski, Radosław; Steffek, Mariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Background : Transthoracic lung ultrasound is relatively poorly known and underestimated by clinicians. Due to lack of radiation, ease of performance and possibility of multiple repetition without risk, transthoracic ultrasound could be a valuable examination especially to monitor intensive care of children who are at risk of respiratory disorders. Aim : The aim of the study is to present the use of transthora- cic ultrasound during postoperative intensive care in children with congenital heart disease after cardiac surgery with extracorporeal circulation. Material and methods : From September 2009 to June 2011 transthoracic sonography was performed in 126 children (average age: 15.7 months) with congenital heart disease who were referred for cardiac surgery with extracorporeal circulation in the Department of Paediatric Cardiac Surgery, Pomeranian Centre of Traumatology in Gdansk. The ultrasound examinations were performed bedside three times: a day before surgery, and on the first and the second postoperative days. Results: Ultrasound images of lungs were entirely correct in all cases before surgery and no abnormalities were observed, whereas on the first or the second day after surgery several ultrasound findings were observed: pleural effusion in 42 cases, pulmonary oedema in 16 cases, pneumothorax in 12 cases, atelectasis in 20 cases (ultrasound image corresponded with pneumonia in 11 cases, collapse of lung tissue in 2 cases, ALI/ARDS in 2 cases, lesions which suggested pulmonary embolism in 5 cases). Conclusion : Transthoracic lung ultrasound could be used during postoperative intensive care after cardiac surgery with extracorporeal circulation to diagnose many causes of life-threatening respiratory disorders and also to monitor therapy.